Chronic Treatment With Psilocybin Decreases Changes in Body Weight in a Rodent Model of Obesity - Huang, Joyce; Pham, Michelle; Panenka, William J.; Honer, William G.; Barr, Alasdair M. (Frontiers in Psychiatry, 2022)
Background: There are currently relatively few effective pharmacological treatments for obesity, and existing ones may be associated with limiting side-effects. In the search for novel anti-obesity agents, drugs that modify central serotonergic systems have historically proven to be effective in promoting weight loss. Psilocin, which is rapidly metabolized from psilocybin, is an agonist at multiple serotonin receptors. In the present study we assessed the effects of psilocybin and a positive control (metformin) on changes in body weight in a rat model of obesity. Methods: Five groups of adult male rats were pre-conditioned with a cafeteria diet until obese (> 600 g) and then treated with either psilocybin (0.1, 1 or 5mg/kg, i.p.), metformin (300mg/kg, p.o.) or vehicle control. Treatments were for 27 consecutive weekdays, and body weights and high calorie food intake were recorded daily. Fasting glucose levels were recorded after 11 days of treatment. At the end of treatment rats completed a glucose tolerance test, and multiple fat pads were dissected out to assess adiposity. Results: The medium dose psilocybin group had to be terminated from the study prematurely. Both the low and high dose psilocybin groups caused a significant decrease in changes in body weight compared to controls. The metformin group produced a greater decrease in change in body weight than either psilocybin groups or controls. Both high dose psilocybin and metformin decreased consumption of the high calorie diet, and exhibited decreased central adiposity. Conclusion: Psilocybin demonstrated modest but significant effects on weight gain. Further study is recommended.